Production of Recombinant Receptor Activator of Nuclear Factor κ B Ligand for in vitro Osteoclastogenesis - Silke Machauer (Hochschule für angewandte Wissenschaften Hamburg, 2014)
Receptor Activator of Nuclear Factor κ B Ligand (RANKL) is a protein that belongs to the family of tumour necrosis factors (TNF) and is one of the two main inducers of osteoclast differentiation. It is therefore used in research facilities that study the molecular and cellular backgrounds of osteoarthritis (OA), a degenerative bone disease that is thought to be associated with a decline in osteoclast number or function. The aim of this work was to produce RANKL, using classical as well as novel methods and techniques of molecular biology and cell culture, including screening for the gene RANKL in leukaemic cell lines, amplification, transformation of Escherichia coli (E. coli) with a plasmid in which RANKL was previously inserted and subsequent analysis of clones, transfection of Chinese Hamster Ovary (CHO) cells with the purified plasmid, and finally qualitative and quantitative analysis of the protein RANKL in the supernatant of a transfected CHO culture.